BOOK REVIEW: IMPOVERISHMENT OF MADURESE SALT FARMERS - Putut Jonggolelono (Jurnal Sosiologi Reflektif, 2023)
Title             : Sosiologi GaramAuthor         : Iskandar DzulkarnainEditor          : Ragil Cahya MaulanaPublisher     : Cantrik PustakaISBN            : 978-623-6063-87-3Year             : 2023